2015
DOI: 10.1007/s00216-015-8979-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical investigation of osteoarthritic human cartilage (ICRS grade) by confocal Raman spectroscopy: a pilot study

Abstract: Biomolecular changes in the cartilage matrix dur-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 56 publications
7
43
0
Order By: Relevance
“…The relationships between ICRS grades and cartilage properties obtained in this study are in agreement with previously observed variations 34 , 35 , therefore supporting the reliability of the scoring. The quantification of PG amount varied slightly between the two methods, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The relationships between ICRS grades and cartilage properties obtained in this study are in agreement with previously observed variations 34 , 35 , therefore supporting the reliability of the scoring. The quantification of PG amount varied slightly between the two methods, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have shown that inflammatory mediators are increased in OA in comparison to healthy subjects, which can be reflected outside the joint tissues in blood plasma and peripheral blood leucocytes . Similar to a number of preceding studies demonstrating increased levels of collagen in OA subjects after analysing cartilage or blood samples, our results also showed a statistically significant increase of the collagen band (1034 cm −1 ) in OA (Fig ) . For instance, the observed increase may be explained by the overexpression of collagen type X, which has been previously found elevated in serum samples of OA patients and has been associated with cartilage degradation and inflammation .…”
Section: Discussionsupporting
confidence: 90%
“…In our previous study, a comparison among ICRS grades of osteoarthritic cartilage was reported that showed a significant reduction in PG content between grades I and III, and between grades II and III, but not between grades I and II [ 5 ]. This means that the change in Young’s modulus shows the same trend as the change in PG content between the ICRS grades I, II, and III.…”
Section: Discussionmentioning
confidence: 99%
“…Early degenerative changes in articular cartilage associated with OA are most often not visible by standard clinical imaging system (e.g., X-ray, MRI, Ultrasound, Arthroscopy). Our previous studies have shown biochemical and structural changes in early stage of osteoarthritic cartilage [ 4 , 5 , 6 ]. In addition to the biochemical and structural changes, the biomechanical properties of the articular cartilage have been shown to evolve with the stage of OA [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%